2016
DOI: 10.1016/j.jshs.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional training on geometric indices of heart rate variability

Abstract: BackgroundGeometric methods provide an analysis of autonomic modulation using the geometric properties of the resulting pattern, and represent an interesting tool in the analysis of heart rate variability (HRV). The aim of this study was to evaluate the impact of functional training on cardiac autonomic modulation in healthy young women using the geometric indices of HRV.MethodsData were analyzed from 29 women, and were stratified into a functional training group (FTG, n = 13; 23.00 ± 2.51 years; 21.90 ± 2.82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 18 publications
0
41
0
2
Order By: Relevance
“…Studies evaluating functional resistance training for 12 weeks in young healthy women showed improvement in quality of life and cardiac autonomic modulation . In the study of Rezende Barbosa et al was observed an increasing the values of RMSSD, SDNN, RR intervals, LFms 2 and HFms 2 ; whereas in another study by Rezende Barbosa et al , an increase was observed in the values of RRtri index, SD1, SD2 and RR intervals …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating functional resistance training for 12 weeks in young healthy women showed improvement in quality of life and cardiac autonomic modulation . In the study of Rezende Barbosa et al was observed an increasing the values of RMSSD, SDNN, RR intervals, LFms 2 and HFms 2 ; whereas in another study by Rezende Barbosa et al , an increase was observed in the values of RRtri index, SD1, SD2 and RR intervals …”
Section: Discussionmentioning
confidence: 99%
“…The movement of people on the site was restricted, in order to reduce interference during collection. The volunteers were asked abstain from consuming alcohol and/or stimulants, such as coffee, tea and chocolate drinks, 24 h before the evaluation …”
Section: Methodsmentioning
confidence: 99%
“…Changes in heart rate defined as heart rate variability (HRV) are normal and expected and indicate a heart's ability to respond to multiple physiological and environmental stimuli as well as to compensate disorders induced by diseases (Silva et al., ; Vanderlei et al., ) . HRV is a simple and not invasive tool that describes the fluctuations between the consecutive heart beats intervals (RR Intervals) and can be used to identify phenomena related to the autonomic nervous system (ANS) (De Rezende Barbosa et al., 2016a,b; Silva et al., ; Vanderlei et al., Giacon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the linear methods that assess HRV we highlight the geometric indices (triangular index [RRtri], triangular interpolation of RR interval histogram [TINN] and Poincaré plot) which convert RR intervals into geometric patterns and allow analyzing HRV through the geometric or graphic properties of the resulting pattern (De Rezende Barbosa et al., 2016a,b; Hoshi et al., , Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology ; Vanderlei et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation